Serological detection of hepatitis B and D virus co-infection among patients attending a tertiary health facility at Maiduguri, Nigeria - Babajide B. Ajayi; Semsari Latbone; Iman U. Igwegbe; Ibrahim M. Kida; Babagana W. Goni; Oyebode O. Samuel; Joshua S. Dawurung; Hamidu M. Ibrahim; Ballah A. Danue; Idris Nasir Abdullahi; Bamidele S. Oderinde (SpringerOpen, 2021)
Abstract Background Hepatitis D virus (HDV) is highly pathogenic, and clinical studies revealed that HDV infection aggravates the natural history of the underlying hepatitis B virus (HBV) infection by progression to cirrhosis that leads to early decompensation of liver function compared with HBV mono-infection. To determine the seroprevalence of HDV among HBsAg-seropositive patients and associated biochemical profiles at Maiduguri, Nigeria, a hospital-based cross-sectional study on 180 sera of patients positive for HBsAg by ELISA were evaluated for anti-HDV, hepatitis B envelop antigen, anti-HBs antibodies and liver enzyme profiles. Results HDV seroprevalence of 3.3% among 180 HBsAg-positive patients. Relatively higher seroprevalence of HDV was observed in males (4.3%) than in females (2.3%). The highest infection rate (20%) was obtained in patients ≥ 56 years. However, no significant association between positive anti-HDV seroprevalence and gender (p > 0.05). Of the 6 (3.3%) anti-HDV-positive patients, only 1 (16.7%) was positive for HBeAg while all were negative for anti-HBs antibodies. The mean level of liver enzyme level of AST and ALT of the anti-HDV-positive patients significantly differ from that of HBsAg mono-infected patients (p ˂ 0.05). However, no significant difference (p < 0.05) between the mean levels of liver enzymes of ALP in anti-HDV-positive and HBsAg mono-infected patients (p ˃ 0.05) was found. Conclusion This study revealed a relatively low presence of HDV in HBsAg-positive patients. Furthermore, HDV-HBV co-infected patients had somewhat worse liver enzyme upregulation. This underscores the need for rapid HDV testing and treatment in HBV-infected patients.